(untitled) (Nepal Journal of Epidemiology, 2021)
Background: The present retrospective study on urinary stone disease in the Uttarakhand state was necessitated as no study has been done yet. Methods: A retrospective study covering a period of about 13 years (2005-18) was conducted on the urinary stones removed from the patients, admitted at Himalayan Institute of Medical Sciences, Dehradun. The incidence of the disease, site of stones in urinary tract upon diagnosis, composition of removed stones and occurrence of a possible co-relationship between the incidence of the urinary stone disease at different times, age, sex, religion of the patients was investigated. Results: The frequency of occurrence of urinary stones in males was found to be almost three times more as compared to their female counterparts. The above trend was consistent over the entire period of the study. Interestingly, in the Muslim and Sikh population of the area, females were found to be less prone to the problem as compared to their Hindu counterparts. However, in all religious groups, 21-40 years old subjects were found to be most susceptible to the problem and approximately 90% of the urinary stones were recovered from the kidneys and primarily composed of calcium oxalate. Conclusion: The co-relationship between the occurrence of urinary stones with age, sex of the patients, their religion & site of stones on diagnosis was found to be statistically significant. Keywords: Urolithiasis, Urinary Stone disease, Urinary calculus, Renal stones.